Functional attributes of evolutionary conserved Arg45 of Wolbachia (Brugia malayi) translation initiation factor-1. (February 2016) - Nag, Jeetendra Kumar; Chahar, Dhanvantri; Shrivastava, Nidhi; Gupta, Chhedi Lal; Bajpai, Preeti; Chandra, Deepak; Misra-Bhattacharya, Shailja
Aim:   Wolbachia is a promising antifilarial chemotherapeutic target. Translation initiation factor-1 (Tl IF-1) is an essential factor in prokaryotes. Functional characterization of Wolbachia's novel proteins/enzymes is necessary for the development of adulticidal drugs.Materials & methods: Mutant, Wol Tl IF-1 R45D was constructed by site directed mutagenesis. Fluorimetry and size exclusion chromatography were used to determine the biophysical characteristics. Mobility shift assay and fluorescence resonance energy transfer were used to investigate the functional aspect of Wol Tl IF-1 with its mutant.Results: Both wild and mutant were in monomeric native conformations. Wild exhibits nonspecific binding with ssRNA/ssDNA fragments under electrostatic conditions and showed annealing and displacement of RNA strands in comparison to mutant.Conclusion: Point mutation impaired RNA chaperone activity of the mutant and its interaction with nucleotides.